Detection of multi-drug resistant Escherichia coli in the urban waterways of Milwaukee, WI - Kappell, Anthony D.; DeNies, Maxwell S.; Ahuja, Neha H.; Ledeboer, Nathan A.; Newton, Ryan J.; Hristova, Krassimira R. (Frontiers in Microbiology, 2015)
Urban waterways represent a natural reservoir of antibiotic resistance which may provide a source of transferable genetic elements to human commensal bacteria and pathogens. The objective of this study was to evaluate antibiotic resistance of Escherichia coli isolated from the urban waterways of Milwaukee, WI compared to those from Milwaukee sewage and a clinical setting in Milwaukee. Antibiotics covering 10 different families were utilized to determine the phenotypic antibiotic resistance for all 259 E. coli isolates. All obtained isolates were determined to be multi-drug resistant. The E. coli isolates were also screened for the presence of the genetic determinants of resistance including ermB (macrolide resistance), tet(M) (tetracycline resistance), and β-lactamases (blaOXA, blaSHV, and blaPSE). E. coli from urban waterways showed a greater incidence of antibiotic resistance to 8 of 17 antibiotics tested compared to human derived sources. These E. coli isolates also demonstrated a greater incidence of resistance to higher numbers of antibiotics compared to the human derived isolates. The urban waterways demonstrated a greater abundance of isolates with co-occurrence of antibiotic resistance than human derived sources. When screened for 5 different antibiotic resistance genes conferring macrolide, tetracycline, and β-lactam resistance, clinical E. coli isolates were more likely to harbor ermB and blaOXA than isolates from urban waterway. These results indicate that Milwaukee’s urban waterways may select for a greater incidence of multiple antibiotic resistance organisms and likely harbor a different antibiotic resistance gene pool than clinical sources. The implications of this study are significant to understanding the presence of resistance in urban freshwater environments by supporting the idea that sediment from urban waterways serves as a reservoir of antibiotic resistance.